One Shock, Many Policy Responses - Mano, Rui (IMF Working Papers; Working Paper ;, 2020)
Policymakers have relied on a wide range of policy tools to cope with capital flow shocks. And yet, the effects and interaction of these policies remain under debate, as does the motivation for using them. In this paper, quantile local projections are used to estimate the entire distribution of future policy responses to portfolio flow shocks for 20 emerging markets and understand the variety of policy choices across the sample. To assuage endogeneity concerns, estimates rely on the fact that global capital flows are exogenous from the viewpoint of any one of these countries. The paper finds that: (i) policy responses to capital flow shocks are heterogeneous across countries, fat-tailed-'extreme' responses tend to be more elastic than 'typical' responses-and asymmetric-'extreme' responses tend to be more elastic with respect to outflows than to inflows; (ii) country characteristics are linked to policy choices-with cross-country differences in forex intervention relating to the size of balance sheet vulnerabilities and the depth of the forex market; (iii) the use of targeted macroprudential policy and capital flows management measures can help 'free the hands' of monetary policy by allowing it to focus more squarely on domestic cyclical developments.